Responsible Fisheries in the Marine Ecosystem - Sinclair, M (CABI, 2014)
This book presents the edited papers from the Conference on Responsible Fisheries in the Marine Ecosystem, which was held from 1–4 October 2001 in Reykjavik, Iceland. The Conference was organized jointly by the Government of Iceland and the Food and Agriculture Organization of the United Nations (FAO), with the co-sponsorship of the Government of Norway. The objectives of the Conference were to: (i) review current knowledge on marine ecosystems of relevance to fisheries management; (ii) identify means by which ecosystem considerations can be included in fisheries management; and (iii) foresee future challenges and outline the relevant strategies to cope with them. In preparing the Conference, a Scientific Committee selected the topics to be addressed and invited experts in the respective scientific fields. Members of the Scientific Committee also undertook a peer review of all presentations.